Dietary Methionine Restriction Regulates Liver Protein Synthesis and Gene Expression Independently of Eukaryotic Initiation Factor 2 Phosphorylation in Mice. Issue 6 (26th April 2017) - Pettit, Ashley P; Jonsson, William O; Bargoud, Albert R; Mirek, Emily T; Peelor, Frederick F; Wang, Yongping; Gettys, Thomas W; Kimball, Scot R; Miller, Benjamin F; Hamilton, Karyn L; Wek, Ronald C; Anthony, Tracy G
Abstract: Background: The phosphorylation of eukaryotic initiation factor 2 (p-eIF2) during dietary amino acid insufficiency reduces protein synthesis and alters gene expression via the integrated stress response (ISR). Objective: We explored whether a Met-restricted (MR) diet activates the ISR to reduce body fat and regulate protein balance. Methods: Male and female mice aged 3–6 mo with either whole-body deletion of general control nonderepressible 2 ( Gcn2 ) or liver-specific deletion of protein kinase R-like endoplasmic reticulum kinase ( Perk ) alongside wild-type or floxed control mice were fed an obesogenic diet sufficient in Met (0.86%) or an MR (0.12% Met) diet for ≤5 wk. Ala enrichment with deuterium was measured to calculate protein synthesis rates. The guanine nucleotide exchange factor activity of eIF2B was measured alongside p-eIF2 and hepatic mRNA expression levels at 2 d and 5 wk. Metabolic phenotyping was conducted at 4 wk, and body composition was measured throughout. Results were evaluated with the use of ANOVA ( P < 0.05). Results: Feeding an MR diet for 2 d did not increase hepatic p-eIF2 or reduce eIF2B activity in wild-type or Gcn2 −/− mice, yet many genes transcriptionally regulated by the ISR were altered in both strains in the same direction and amplitude. Feeding an MR diet for 5 wk increased p-eIF2 and reduced eIF2B activity in wild-type but not Gcn2 −/− mice, yet ISR-regulated genes altered in both strains similarly. Furthermore, the MR diet reduced mixed and cytosolic but not mitochondrial protein synthesis in both the liver and skeletal muscle regardless of Gcn2 status. Despite the similarities between strains, the MR diet did not increase energy expenditure or reduce body fat in Gcn2 −/− mice. Finally, feeding the MR diet to mice with Perk deleted in the liver increased hepatic p-eIF2 and altered body composition similar to floxed controls. Conclusions: Hepatic activation of the ISR resulting from an MR diet does not require p-eIF2. Gcn2 status influences body fat loss but not protein balance when Met is restricted.